2009
DOI: 10.1073/pnas.0812536106
|View full text |Cite
|
Sign up to set email alerts
|

The cAMP binding protein Epac regulates cardiac myofilament function

Abstract: In the heart, cAMP is a key regulator of excitation-contraction coupling and its biological effects are mainly associated with the activity of protein kinase A (PKA). The aim of this study was to investigate the contribution of the cAMP-binding protein Epac (Exchange protein directly activated by cAMP) in the regulation of the contractile properties of rat ventricular cardiac myocytes. We report that both PKA and Epac increased cardiac sarcomere contraction but through opposite mechanisms. Differently from PKA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
73
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 36 publications
(49 reference statements)
5
73
0
2
Order By: Relevance
“…Cazorla et al . have shown that Epac activates phospholipase C, which hydrolyzes phosphatidylinositol bisphosphate to produce diacylglycerol and inositol triphosphate (IP 3 ), leading to PKC activation or IP3 receptor‐dependent Ca 2+ release (Cazorla et al, 2009). Furthermore, Li et al .…”
Section: Discussionmentioning
confidence: 99%
“…Cazorla et al . have shown that Epac activates phospholipase C, which hydrolyzes phosphatidylinositol bisphosphate to produce diacylglycerol and inositol triphosphate (IP 3 ), leading to PKC activation or IP3 receptor‐dependent Ca 2+ release (Cazorla et al, 2009). Furthermore, Li et al .…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Furthermore, independently of its effect on sarcoplasmic reticulum function, Epac1 was reported to act on the myofilament compartment where it regulates the phosphorylation of sarcomeric proteins to increase myofilament Ca 2+ sensitivity. 33 Finally, Epac1 was previously found in the mitochondrion of Epac1-transfected COS-7 cells in a cell cycle-dependent manner, 34 although it was not linked to any biological function. Here we found that Epac1 is indeed localized in the mitochondrion of cardiomyocytes, where it exerts its regulatory role on cardiomyocyte cell death via its activation by cAMP produced by sAC.…”
Section: Discussionmentioning
confidence: 99%
“…43 Although less well established, CaMKII also modulates phosphorylation and function of sarcomeric regulatory proteins, such as cardiac myosin-binding protein-C and cardiac troponin-I. [34][35][36][37] A role for CaMKII in myofilament protein phosphorylation may underlie part of the deterioration in diastolic function reported in pressure-overload CaMKIIδ-knockout mice. 37 In this work, we demonstrated that the myofilament protein titin is a main substrate of CaMKII.…”
Section: Discussionmentioning
confidence: 99%
“…23,27 At the cardiac myofilament level, CaMKII phosphorylates myosin-binding protein-C and troponin-I, alters the rates of force development and relaxation, and modulates calcium sensitivity. [34][35][36][37] In this study, we demonstrate that CaMKIIδ indeed phosphorylates cardiac titin and affects diastolic function by altering titin-based stiffness. We identify various CaMKII-dependent phosphosites along titin by quantitative mass spectrometry (MS), confirm specific sites within the N2Bus and PEVK spring elements of mouse and human titin, and show that CaMKII-mediated phosphorylation reduces cardiomyocyte F passive .…”
mentioning
confidence: 99%